Mouth breathing, another risk factor for asthma: the Nagahama Study. Issue 7 (1st April 2016) - Izuhara, Y.; Matsumoto, H.; Nagasaki, T.; Kanemitsu, Y.; Murase, K.; Ito, I.; Oguma, T.; Muro, S.; Asai, K.; Tabara, Y.; Takahashi, K.; Bessho, K.; et al.
Abstract: Background: Allergic rhinitis, a known risk factor for asthma onset, often accompanies mouth breathing. Mouth breathing may bypass the protective function of the nose and is anecdotally considered to increase asthma morbidity. However, there is no epidemiological evidence that mouth breathing is independently associated with asthma morbidity and sensitization to allergens. In this study, we aimed to clarify the association between mouth breathing and asthma morbidity and allergic/eosinophilic inflammation, while considering the effect of allergic rhinitis. Methods: This community‐based cohort study, the Nagahama Study, contained a self‐reporting questionnaire on mouth breathing and medical history, blood tests, and pulmonary function testing. We enrolled 9804 general citizens of Nagahama City in the Shiga Prefecture, Japan. Results: Mouth breathing was reported by 17% of the population and was independently associated with asthma morbidity. The odds ratio for asthma morbidity was 1.85 (95% CI, 1.27–2.62) and 2.20 (95% CI, 1.72–2.80) in subjects with mouth breathing alone and allergic rhinitis alone, which additively increased to 4.09 (95% CI, 3.01–5.52) when mouth breathing and allergic rhinitis coexisted. Mouth breathing in nonasthmatics was a risk for house dust mite sensitization, higher blood eosinophil counts, and lower pulmonary function after adjusting for allergic rhinitis. Conclusion: Mouth breathing may increase asthma morbidity, potentially through increased sensitization to inhaled allergens, which highlights the risk of mouth‐bypass breathing in the 'one airway, one disease' concept. The risk of mouth breathing should be well recognized in subjects with allergic rhinitis and in the general population.